2011
DOI: 10.1111/j.1467-6435.2011.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Works Councils and Learning: On the Dynamic Dimension of Codetermination

Abstract: This study provides the first econometric analysis on the dynamic dimension of establishmentlevel codetermination in Germany. We hypothesize that learning implies a change in the nature and scope of codetermination over time. Using unique data from small-and medium-sized establishments, our empirical analysis provides strong evidence that learning indeed plays a crucial role in the functioning of works councils. First, the probability of an adversarial relationship between management and works council is decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 38 publications
1
50
1
2
Order By: Relevance
“…For a case in point, seeJirjahn et al (2011). They provide a theoretical discussion of how the relationship between management and a formal employee representation evolves over time and how it may increase firm productivity.…”
mentioning
confidence: 98%
“…For a case in point, seeJirjahn et al (2011). They provide a theoretical discussion of how the relationship between management and a formal employee representation evolves over time and how it may increase firm productivity.…”
mentioning
confidence: 98%
“…Works council strategies also vary considerably from one firm to another, as Kotthoff (2013) emphasises. Sometimes this may be due to the economic situation, but it can also be affected by their long-term experience of dealing with management, as shown by Jirjahn et al (2011). Thus, one of the long-standing strengths of the German system has been its adaptability, although much of the current debate in Germany focuses on whether its limits have been reached.…”
Section: Institutional Change and Prospectsmentioning
confidence: 99%
“…Finally, the institutions themselves take time to win the confidence of the parties both as concerns their effectiveness and their trustworthiness. Jirjahn et al (2011) found that mutual confidence between management and works councils takes time to develop. This should not be surprising as employee representatives have to find common ground with management while maintaining their credibility with their constituents, which takes time.…”
Section: Employee Voice and The Stability Of Cooperationmentioning
confidence: 99%
“…We hypothesize that the resistance of employers is greater as the management's decision horizon becomes more short-term. It would be fruitful to extend the dynamic analysis by Jirjahn et al (2011) and Müller and Stegmaier (2016) to other fields, such as profitability and wages, to obtain a more complete picture.…”
Section: Short-term Orientationmentioning
confidence: 99%